Clinical features of dermatomyositis associated with anti-MDA5 antibodies by age. Issue 1 (2nd January 2021) - Yamaguchi, Koichi; Yamaguchi, Aya; Onuki, Yuji; Itai, Miki; Kashiwagi, Chiharu; Takehara, Kazutaka; Aoki, Shuhei; Kanaya, Azusa; Taguchi, Kohei; Umetsu, Kazue; Oshima, Kazuma; Uchida, Megumi; et al.
Abstract: Objectives: Anti-melanoma differentiation-associated gene 5 (MDA5) autoantibody-positive and age at onset ≥60 years are poor prognosis factors in polymyositis (PM) and dermatomyositis (DM) associated with interstitial lung disease (ILD) among Japanese patients. However, the influence of age on the clinical features of anti-MDA5 autoantibody-positive patients with DM remains unclear. Methods: We retrospectively examined 40 patients with DM and anti-MDA5 autoantibodies according to age. We compared patients aged <60 and ≥60 years with respect to clinical features including laboratory test findings, high-resolution lung computed tomography data, treatment content, and complications such as infections and prognosis. We also examined clinical features between surviving and deceased patients in the older patient group. Results: Of 40 enrolled patients, 13 were classified as old and 27 as young. Older patients had significantly fewer clinical symptoms including arthralgia/arthritis ( p  < .01), skin ulceration ( p  = .02), and higher mortality than younger patients ( p  = .02) complicated with rapidly progressive ILD (RP-ILD), combination immunosuppressive therapy, and strictly controlled infections. Conclusion: Clinical features and mortality of anti-MDA5 autoantibody-positive DM patients were influenced by age. Patients aged ≥60 years had a worse prognosis, and combination immunosuppressive therapy was often ineffective for RP-ILD in older patients.